2012
DOI: 10.21083/partnership.v7i1.1646
|View full text |Cite
|
Sign up to set email alerts
|

Access to and Usage of Information among Rural Communities: a Case Study of Kilosa District Morogoro Region in Tanzania

Abstract: The study investigates how rural communities in Kilosa District of Morogoro region in Tanzania access and use information. Specifically, the study identifies the information needs of rural people, determines the factors influencing the choice of information source, and assesses the appropriateness of the information sources based on usefulness and preference. Choice of the study area was based on the availability of multiple information sources information seekers could consult. Simple random sampling techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 0 publications
7
35
1
Order By: Relevance
“…Study by Ronald et al (2014) and Mtega (2012) realised that, rural area natives like farmers are not accessing sufficient information which could help them in decision making and yield improvement. There are a number of studies which focused on analysis of factors which influence information accessibility in rural community.…”
Section: Information Access In Rural Communities Of Tanzania Is Very mentioning
confidence: 99%
See 1 more Smart Citation
“…Study by Ronald et al (2014) and Mtega (2012) realised that, rural area natives like farmers are not accessing sufficient information which could help them in decision making and yield improvement. There are a number of studies which focused on analysis of factors which influence information accessibility in rural community.…”
Section: Information Access In Rural Communities Of Tanzania Is Very mentioning
confidence: 99%
“…For example, higher penetration of smart phones in rural area implies that there is a higher accessibility of information since rural people can surf online and get more information. Also, the presence of electricity supports uses of radio, TV and computer since more information can be accessed (Mtega, 2012).…”
Section: Information Access In Rural Communities Of Tanzania Is Very mentioning
confidence: 99%
“…Several studies, such as Momodu (2002), Kalusopa (2005), Mtega (2012), Benard , Dulle and Ngalapa (2014), Owolade and Kayode's (2012), report the information practices of various rural populations including farmers, snail farmers, rural women, and cottage industry professionals. This section briefly illustrates the core findings of some of the studies conducted on rural dwellers in various countries.…”
Section: Information Practices Of Rural Dwellers Except Fishermenmentioning
confidence: 99%
“…In Zambia, a study by Kalusopa (2005) reports farm management, dairy management, and poultry equipment and technology are the three essential areas of information needs of small-scale farmers who participated in the study. In Tanzania, a study by Mtega (2012) reports that information related to market, health, political, credit, leisure, and agricultural husbandry practices were some of the information need of the rural population studied. The participants of the Mtega's (2012) study indicated radio, face-to-face communication, mobile phones, television, and newspapers as some of their information sources.…”
Section: Information Practices Of Rural Dwellers Except Fishermenmentioning
confidence: 99%
See 1 more Smart Citation